Konsep Restoratif Justice Terhadap Pelaku Tindak Pidana Anak Wujud Implementasi Nilai Islam dan Kearifan Lokal - Haniyah, Haniyah (Proceedings of Annual Conference for Muslim Scholars, 2024)
The phenomenon of children as perpetrators of crimes, is increasing and in children's courts, when children commit criminal acts, the system of restorative justice applies as in criminal law, while children are valuable assets, for parents, families and the state, The purpose of the research is to find out whether the concept of restorative justice does not contradict Islamic values and local wisdom, the research is a normative research with a legal and conceptual approach, The results of the study show that the concept of restorative justice as an action that is very appropriate to be applied to child offenders, considering that children are the shoots of the nation that must be maintained as the next generation of the nation in addition to the philosophical value The concept of restorative justice has long been applied in solving every problem in the majority Muslim society in Indonesia.